Propensity matched comparative analysis of survival following chemoradiation or radical cystectomy for muscle‐invasive bladder cancer. (22nd January 2018) - Ritch, Chad R.; Balise, Raymond; Prakash, Nachiketh Soodana; Alonzo, David; Almengo, Katherine; Alameddine, Mahmoud; Venkatramani, Vivek; Punnen, Sanoj; Parekh, Dipen J.; Gonzalgo, Mark L.
Abstract : Objective: To compare survival outcome between chemoradiation therapy (CRT) and radical cystectomy (RC) for muscle‐invasive bladder cancer (MIBC). Patients and Methods: We conducted a retrospective analysis of patients with MIBC (≥cT2, N0, M0) in the National Cancer Database (2004–2013). CRT was defined as a radiation dose of ≥40 Gy and chemotherapy within 90 days of radiation. Descriptive statistics were used to compare groups. RC and CRT patients were propensity matched. Kaplan–Meier analysis was used to compare overall survival (OS). Multivariable Cox regression was used to determine predictors of survival. Results: In all, 8 379 (6 606 RC and 1 773 CRT) patients met the inclusion criteria and 1 683 patients in each group were propensity matched. On multivariable extended Cox analysis, significant predictors of decreased OS were age, Charlson‐Deyo Comorbidity score of 1, Charlson‐Deyo Comorbidity score of 2, stage cT3–4, and urothelial histology. CRT was associated with decreased mortality at year 1 (hazard ratio [HR] 0.84, 95% confidence interval [CI] 0.74–0.96; P = 0.01), but at 2 years (HR 1.4, 95% CI 1.2–1.6; P < 0.001) and 3 years onward (HR 1.5, 95% CI 1.2–1.8; P < 0.001) CRT was associated with increased mortality. The 5‐year OS was greater for RC than for CRT (38% vs 30%, P = 0.004). Conclusions: Initially after treatment for MIBC the risk of mortality is lower with CRT compared to RC. However, at ≥2 years after treatment the mortality risk favours RC. Patients who are suitable surgical candidates, with a low risk of morbidity, may be better served by RC.